2020
DOI: 10.14569/ijacsa.2020.0110754
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Use of Technological Tools in University Higher Education using the Soft Systems Methodology

Abstract: This article analyzes the professional training of students according to the current situation. Students are experiencing a new modality of study due to the Covid-19 and specialists have to evaluate which would be the best solutions in order that students achieve greater understanding, because they are one of the most affected today. Therefore, we will be able to analyze in a detailed way each one of the causes that our problem presents to evaluate and thus to be able to obtain the different points of view of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Regarding this, Almenara and Gimeno [30] pointed out that almost 98% of teachers are located only at a first level of mastery of virtual tools, making use only at an elementary level of information and communication technologies (ICT). On the other hand, Bernaola et al [31] it is indicated that the training and development of digital skills in teachers were accelerated due to the pandemic and virtual teaching, reflecting that 83.0% of teachers participated in virtual courses and 67.0 % were trained in the use of virtual tools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding this, Almenara and Gimeno [30] pointed out that almost 98% of teachers are located only at a first level of mastery of virtual tools, making use only at an elementary level of information and communication technologies (ICT). On the other hand, Bernaola et al [31] it is indicated that the training and development of digital skills in teachers were accelerated due to the pandemic and virtual teaching, reflecting that 83.0% of teachers participated in virtual courses and 67.0 % were trained in the use of virtual tools.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of teaching performance in higher education has been carried out by various procedures and methods, such as: teacher selfassessment, assessment by peers and academic managers, and assessment by students [28], [29]. It can be said that knowing the perception of students in relation to teaching through virtual tools allows measuring the degree of satisfaction with the quality of distance teaching-learning, which today represents a continuous effort of each one of higher education institutions [30], [31].…”
Section: Introductionmentioning
confidence: 99%
“…Guiding an intervention by objectives based on stakeholders' values can result in consequences more aligned with stakeholders' expectations. Recent applications of SSM like Bernaola, et al (2020), Khayame & Abdeljawad (2020), de Lima Medeiros, Terra & Passador (2020), Sharma, et al (2019), Radfar, et al (2014 and Hanafizadeh & Ghamkhari (2019) focus effort in a few transformations (or in a single transformation) but they do not provide details about any other transformations that may be discarded.…”
Section: Discussion On the Framework Proposed And Its Applicationmentioning
confidence: 99%
“…In Peru, there were educational problems in the teaching of children during the COVID-19 pandemic [8]. They had student delays because virtual classes were not proposed.…”
Section: Introductionmentioning
confidence: 99%